Theoretical review of psychosemantic studies of military servants - Мозговий, В. І. (Psychological Counseling and Psychotherapy, 2018)
The article analyzes psychosemantic researches of servicemen in Ukraine and Russia. The study proposed solutions to the following tasks: to analyze the main content of psychosemantic research with the military and determine the focus of further research with the military. The general analysis of psychosemantic studies of servicemen can be divided into three groups: The first group is the study of the peculiarities of the personal and semantic sphere of servicemen, as well as professional identity. The second group is the study of the behavior of the military, the features of their communication and motivation to serve. Performance of their official duties due to the regularity and hierarchy of military service. The third is the study of the formation of social representations about the image of the military and the army in general. Familiarization with the results and conclusions of the psychosemantic researches of military personnel, received by specialists, allowed to determine the focus of further research in this direction. In further studies, in our opinion, the actual question arises of the study of social representations of conscripts and soldiers of the regular service for the army and the military, as well as its impact on society as an important social institution. The study of these social representations can have a qualitative effect on the formation of young people's motivation to undergo military service, their adaptation to military activity, and the quality of their military professional tasks. The need for conducting these studies is determined by the dynamics of society development, the peculiarities of the modern worldview and the importance of military structures for each country.